Evolution and lessons from an integrated service delivery network in North West Syria - Sophie Witter; Karin Diaconu; Ibrahim Bou-Orm; Zeina Jamal; Zubin Cyrus Shroff; Abdulbaki Mahmoud; Mahmoud Daher; Vinod Varma (Conflict and Health, 2023)
Abstract Background Northwest Syria (NWS) is a complex and extremely fragile operating environment, with more than 2.8 million people needing humanitarian assistance. To support a common standard of care delivery and enable coordination among the multiple providers in NWS, WHO developed an Essential Health Services package (EHSP) in 2016-17 and subsequently supported a facility network model to deliver the EHSP. This article provides an evaluation of the network to date, aiming to inform further development of the network and draw wider lessons for application of similar approaches in complex emergency settings. Methods This mixed method study included document review, participatory, qualitative and quantitative data, gathered in the first half of 2021. Participatory data came from two group model building workshops with 21 funders and implementers. Semi-structured interviews with 81 funders, health professionals and community members were also conducted. Analyses of the workshops and interviews was inductive, however a deductive approach was used for synthesising insights across this and the document review. The final component was a survey of health providers (59 health care professionals) and service users (233 pregnant women and 214 persons living with NCDs) across network and other comparable facilities, analysed using routine descriptive and inferential statistics. Findings across all methods were triangulated. Results The study finds that the network and its accompanying essential service package were relevant to the dynamic and challenging context, with high but shifting population needs and multiple uncoordinated providers. Judged in relation to its original goals of comprehensive, coordinated services, equitable access and efficient service delivery, the data indicate that gains have been made in all three areas through the network, although attribution is challenging, given the complex environment. The context remains challenging, with shifting boundaries and populations displaced by conflict, difficulties in retaining staff, the need to import medicines and supplies across borders, and governance gaps. Conclusion This study adds to a very limited literature on coordinated network approaches used to raise care quality and improve referrals and efficiency in a complex emergency setting. Although areas of ongoing challenge, including for sustainability, are noted, the network demonstrated some resilience strategies and can provide lessons for other similar contexts.